Effect of Geographical Location and Type of Extract on Total Phenol/Flavon Contents and Antioxidant Activity of Different Fruits Extracts of Withania somnifera - Adhikari, Lokesh; Kotiyal, Rupali; Pandey, Mukesh; Bharkatiya, Meenakshi; Sematy, Ajay; Semalty, Mona (Current Drug Discovery Technologies, 2020)
Background: Withania somnifera (family solanaceae) is a well-investigated medicinal plant which is also called Indian ginseng due to its wide spectrum of medicinal properties. The contents and activity of the plant may vary depending on the habitat and part of the plant and the solvent used for extraction. The present study deals with the comparative chemical analysis and in vitro antioxidant activity of methanolic fruits extracts and its subfractions (in ethyl acetate, butanol and water) of W. somnifera collected from two different geographical locations. Methods: In the present study, Withania somnifera fruits were collected from two different geographical locations (Uttarakhand and Rajasthan). The different fruit extracts were prepared and studied for total phenolic contents and total flavone contents. The in vitro antioxidant activity was assessed by DPPH free radical scavenging assay and peroxide scavenging assay. Results: Methanol extract of W. somnifera Uttarakhand and ethyl acetate subfraction of W. somnifera Rajasthan showed the highest amount of Total Phenolic Contents (TPC). In W. somnifera Uttarakhand, ethyl acetate extract showed the highest amount of Total flavonoids while in W. somnifera Rajasthan, methanol extract was found to be the richest in flavonoids. Methanolic extract of W. somnifera Uttarakhand showed the highest free radical scavenging activity while in W. somnifera Rajasthan, the highest antioxidant activity was shown by the methanolic extract followed by butanolic extract, water extract and then ethyl acetate. In the peroxide scavenging assay of antioxidant activity, water extract of W. somnifera Uttarakhand showed the highest activity, while in W. somnifera Rajasthan, ethyl acetate extract showed highest scavenging activity. Conclusion: It was concluded that the geographical location exerts a vital effect on the presence of active constituents and also on the antioxidant potential of W. somnifera.
Keywords: Phenolic contents